Pergeseran Bahasa Sentani dalam Era Globalisasi - Neni Sihombing (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Language dislocation possible happens in a heterogenic environment, adding it was supported by globalization influent that is enteringby more open from every part. So unsurprising that language dislocate was happen. It is happening, sure it is being keep alive efforts by the speaker of that language. The problem can be happen on keep alive language is no enheriting language mother using from the parents to their children. It can be dislocating East Sentani language; futhermore it can be lost at some generation.